2011
DOI: 10.1177/0021998311398386
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic crash model for energy absorption in braided composite materials - Part II: Implementation and verification

Abstract: A dynamic crash model is developed and implemented to model the failure behavior and energy absorption of braided composite structures. Part I describes the development and theoretical foundation of a viscoplastic material model that captures the rate-dependent behavior present in braided composite materials. Part II presents the implementation of the model into a finite element model program and the experimental results for tubes crushed from quasi-static to 4000 mm/s rates used to verify the model. Energy ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Gui et al [63] found that SEA for glass/epoxy tubes increases with decreasing braiding angle. Xiao et al [64] and Flesher et al [65] depicted that SEA increases with increasing braiding angle for carbon/epoxy tubes. Okano et al [61] showed that SEA increases with increasing braiding angle for carbon/epoxy tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Gui et al [63] found that SEA for glass/epoxy tubes increases with decreasing braiding angle. Xiao et al [64] and Flesher et al [65] depicted that SEA increases with increasing braiding angle for carbon/epoxy tubes. Okano et al [61] showed that SEA increases with increasing braiding angle for carbon/epoxy tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Laminate composite material models are presented despite that woven composite is more frequently used. Woven material models are also being used for large deformation and crush simulations [6]. This paper address mostly the linear response of the MES Composites cells and modules.…”
Section: Composite Facesheetmentioning
confidence: 99%
“…Beard successfully simulated the quasi-static crushing of plug-initiated triaxially braided circular and square tubes using a micromechanical model incorporated into ABAQUS/Implicit [8][9][10]. The model was later incorporated into ABAQUS/Explicit and used to model dynamic crushing processes by Flesher [11][12][13]. Castejon [14] made effort to model the crush behavior of chamfered braided composite tubes.…”
Section: Introductionmentioning
confidence: 99%